First Report Regarding the Simultaneous Molecular Detection of Anaplasma marginale and Theileria annulata in Equine Blood Samples Collected from Southern Punjab in Pakistan - Asif, Muhammad; Parveen, Asia; Ashraf, Sehrish; Hussain, Mureed; Aktas, Munir; Ozubek, Sezayi; Iqbal, Furhan (Springer Int Publ Ag, 2020)
Aim The present study was designed to check the molecular detection of Anaplasma marginale and Theileria annulata in blood samples of horses and donkeys collected from Dera Ghazi Khan District in Punjab and to document their phylogenetic origin and their association with studied epidemiological factors (sex and age) and complete blood count parameters, if any. Methods and results A total of 195 blood samples were collected from apparently healthy horses (N = 141) and donkeys (N = 54). A. marginale DNA was detected by PCR in 4.9% (7/141) horse and in 9.2% (5/54) of donkey blood samples. Prevalence of T. annulata was 5.6% (8/141) and 11.1% (6/54) in horse and donkey samples, respectively. While 1.4% (N = 2) horses and 3.7% (N = 2) donkeys were found co-infected with both parasites. Representative amplicon for both parasites was confirmed by DNA sequenced and partial DNA sequence of the major surface protein-1b encoding gene of A. marginale and cytochrome b gene from T. annulata were submitted to the GenBank database under the accession number MK792344-MK792348. Epidemiological data analysis revealed that female horses were more prone to A. marginale (P = 0.02) while female donkeys were more susceptible to A. marginale (P < 0.001) and T. annulata (P < 0.001) infection. It was observed that horse and donkey infected either with Anaplasma marginale or Theileria annulata had significantly disturbed red and white blood cell counts and their associated parameters. Conclusion This is a first ever study regarding molecular detection of A. marginale and T. annulata in equine blood samples from Pakistan. We recommend that this multiplex PCR protocol should be used for the detection of Anaplasma marginale and Theileria annulata in livestock for their proper diagnosis and treatment.
Keywords: Theileria annulata; Anaplasma marginale; Multiplex PCR; Equines; Phylogenetic analysis